Unproductive Public Expenditures : A Pragmatic Approach to Policy Analysis. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Public expenditure policy, together with efforts to raise revenue,is at the core of efficient and equitable adjustment. Public expenditureproductivity has critical implications for fiscal adjustment, particularly as the competition for limited public resources intensifies.By providing a framework for defining and analyzing public expenditureproductivity and unproductive expenditures, this pamphlet discusseshow economic policymakers may approach these issues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet